Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let A, B and C are independent events. How am I supposed to prove that:

  1. A′, B′ and C′ are independent.

  2. A, B′ and C′ , are independent.

  3. A, B and C' are independend.

This is my approach:

for Nr 3.

$P(ABC') = P(A)P(B)P(C').$ But $P(AB)=P(ABC)+P(ABC')$ and using independence $P(A)P(B) = P(A)P(B)P(C)+ P(ABC')$, therefore $P(A)P(B)(1-P(C))=P(ABC')$, $P(ABC') = P(A)P(B)P(C')$.

for Nr 2.

$P(AB'C') = P(A)P(B')P(C')$. But $P(AC')=P(ABC')+P(ABC')$ and using independence $P(A)P(C') = P(A)P(B)P(C')+ P(A B' C')$, therefore $P(A)P(C')(1-P(B))=P(AB' C')$, $P(AB'C') = P(A)P(B')P(C')$.

And for Nr 1.

$P(A'B'C') = P(A')P(B')P(C')$. But $P(A'B')=P(A'B' C )+P(A'B'C')$ and using independence $P(A')P(B') = P(A')P(B')P(C)+ P(A'B'C')$, therefore $P(A')P(B')(1-P(C))=P(A'B'C')$, $P(ABC') = P(A')P(B')P(C')$.

What do you think people? is this way of proving right?

share|cite|improve this question
Read the definition of independence carefully and look through this answer! – user21436 Mar 27 '12 at 11:34
Hmmm, i see ! Thanks for your answer. what troubles me is that there are 3 events and not 2 like the most cases! Well i ll look into it now! thanks – Adrian Carter Mar 27 '12 at 12:00
Hint: Try to prove first that $A$, $B$ and $C'$ are inpedendent, than 2. and finally 1 (using what you've done in step one). – martini Mar 27 '12 at 12:26
Hey martini!! thanks thanks! – Adrian Carter Mar 27 '12 at 13:43
I've merged the previous incarnation of the question with this one. – Willie Wong Mar 29 '12 at 21:44

You have shown this, but for clarity, using independence you have $$\Pr(ABC)=\Pr(A)\Pr(B)\Pr(C)$$ and $$\Pr(AB)=\Pr(A)\Pr(B)$$ so $$\Pr(ABC')=\Pr(AB)-\Pr(ABC) $$ $$=\Pr(A)\Pr(B)- \Pr(A)\Pr(B)\Pr(C) $$ $$= \Pr(A)\Pr(B)(1-\Pr(C)) $$ $$=\Pr(A)\Pr(B)\Pr(C')$$

so $A$, $B$ and $C'$ are independent events.

Since this is all commutative, as martini says, you can then derive (2) and (1).

share|cite|improve this answer
^ Very nice! actually it makes much more sense to me now, clarity, thats exactly what i needed! Thanks! – Adrian Carter Mar 28 '12 at 23:23
But i still can understand this --> WHY Pr(A)Pr(B)−Pr(A)Pr(B)Pr(C) =Pr(A)Pr(B)(1−Pr(C)) ? – Adrian Carter Mar 28 '12 at 23:34
@Adrian: In general $x\times y - x\times y \times z = x\times y \times (1-z)$ because of the common factor of $x \times y$ – Henry Mar 28 '12 at 23:36
Actually, depending on what one assumes, proving that $\Pr(ABC^\prime)=\Pr(A)\Pr(B)\Pr(C^\prime)$ is not quite sufficient to prove that $A$, $B$, $C^\prime$ are independent. It is also necessary to assert (or remind the reader) that the other conditons $\Pr(AB)=\Pr(A)\Pr(B)$, $\Pr(AC^\prime)=\Pr(A)\Pr(C^\prime)$, $\Pr(BC^\prime)=\Pr(B)\Pr(C^\prime)$ follow from the results on pairwise independence of $A, B, C$. – Dilip Sarwate Mar 29 '12 at 3:32

Your answer/proof is incomplete. In order to assert that three events $D$, $E$, $F$ are mutually independent, you have to verify that four equations hold: $$\begin{align*} P(DEF) &= P(D)P(E)P(F)\\ P(DE) &= P(D)P(E)\\ P(DF) &= P(D)P(F)\\ P(EF) &= P(E)P(F)\\ \end{align*}$$ Taking $D=A$, $E=B$, $F=C^\prime$, you have verified the first of the four equations above. Now you need to say that $P(AB)=P(A)P(B)$ follows from the independence of $A$ and $B$, and either prove that $P(AC^\prime) = P(A)P(C^\prime)$ and $P(BC^\prime) = P(B)P(C^\prime)$, or assert that these follow from the independence of $A$ and $C$, and $B$ and $C$ respectively if you have done these kinds of calculations previously.

Another definition of independence of $n$ events $A_i$ is that all $2^n$ equations $$P(A_1^*A_2^*\cdots A_n^*) = P(A_1^*)P(A_2^*)\cdots P(A_n^*)$$ must hold, where each $A_i^*$ stands for either $A_i$ or $A_i^\prime$, the same on both sides of the equation. With this definition, the statements to be proved in the OP's problem are true by definition and there is nothing to prove.

share|cite|improve this answer
^ quite enlightening post there, this is what i missed, finally , thanks, it seems that i totally forgot pairwise independence. Thats why, i had a weird feeling that my proof was just not right... Thanks! – Adrian Carter Mar 29 '12 at 13:59

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.